2012
DOI: 10.4321/s1130-01082012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis C in Spain: a retrospective study of 131 cases

Abstract: Background and aims: the management of acute hepatitis C (AHC) is controversial. We have conducted a retrospective study to determine the epidemiological and biochemical aspects, the genotypes, the spontaneous clearance of HCV (SVC), and the treatment responses in patients with AHC.Methods: we have retrospectively collected data from 131 patients with AHC from 18 Spanish hospitals.Results: the mean age was 43 ± 16 years (17-83), 69% were symptomatic. The causes of infection were nosocomial in 40% and intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
1
3
0
4
Order By: Relevance
“…Although the ages of our patients were similar to those reported in other aHC series [Kamal et al, ; Perez‐Alvarez et al, ; Bunchorntavakul et al, ], 44% of our patients (28 individuals) were 50 years or older at the time of infection. This rather high proportion of older patients may be related to the predominance of a nosocomial transmission source; it has been previously suggested that this risk factor prevails in older subjects (>50 years of age) [Perez‐Alvarez et al, ]; patients reporting sexual‐ or drug use‐related exposure were significantly younger. The small percentage of patients who declared drug use as a risk factor is concordant with previous reports; intravenous drug addiction related to HCV acquisition has been traditionally considered infrequent in South America [Findor et al, ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although the ages of our patients were similar to those reported in other aHC series [Kamal et al, ; Perez‐Alvarez et al, ; Bunchorntavakul et al, ], 44% of our patients (28 individuals) were 50 years or older at the time of infection. This rather high proportion of older patients may be related to the predominance of a nosocomial transmission source; it has been previously suggested that this risk factor prevails in older subjects (>50 years of age) [Perez‐Alvarez et al, ]; patients reporting sexual‐ or drug use‐related exposure were significantly younger. The small percentage of patients who declared drug use as a risk factor is concordant with previous reports; intravenous drug addiction related to HCV acquisition has been traditionally considered infrequent in South America [Findor et al, ].…”
Section: Discussionsupporting
confidence: 86%
“…Both in developed and developing countries, nosocomial transmission of aHC has been extensively reported, particularly since the incidence of HCV infection due to blood product transfusions and intravenous drug use has decreased [Maheshwari et al, ]. In a recent study conducted in Germany, medical procedures were the primary suspected source of infection [Gerlach et al, ]; similarly, in a Spanish retrospective analysis of 131 patients, 40% of patients reported a non‐transfusion related nosocomial source of infection [Perez‐Alvarez et al, ]. In a prior South American survey conducted in Brazil, the main risk factors for HCV transmission in aHC patients were related to hospital procedures or admission [Ferreira Ade et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…For 11 studies [20,22-25,27,28,30,33,36,37] included in the review, treatment uptake levels could be calculated specifically for current and former PWID (Table 5). (Other studies had study populations that included non-injecting drug users.)…”
Section: Resultsmentioning
confidence: 99%
“…The fact that hepatic cytolysis enzymes have decreased or tended to normalize, as occurred during the period of hospitalization of this patient, does not necessarily mean that the infection will resolve spontaneously. In fact, although some studies reveal spontaneous viral clearance around 50% [[9], [10], [11], [12], [13], [14]], and others reveal that symptomatic patients are more likely to spontaneous clearance [15,16], the truth is that acute phase provide an opportunity for early treatment of patients before they progress to chronicity.…”
Section: Discussionmentioning
confidence: 99%